Context matters in smoking prevention: evaluating smoke-free school hours in Danish vocational schools. (26th April 2023) - Danielsen, Dina; Jensen, Tina S; Kjeld, Simone G; Bast, Lotus S; Andersen, Susan
Summary: Youth is a crucial period for smoking preventive interventions. School-based interventions targeting the policy level and the sociocultural processes of smoking show promising effects in reducing smoking uptake and prevalence. This study presents findings from the qualitative process evaluation of a smoking preventive intervention, Focus, in the vocational school (VET) setting. Specifically, the study focused on contextual factors affecting the implementation of smoke-free school hours (SFSH). Participant observations and focus groups were conducted in four VETs during the implementation period October–December 2018. The data encompass participant observation field notes ( n = 21 school days), student focus groups ( n = 8) (aged 16–20), teacher focus groups ( n = 5) and semi-structured individual interviews with VET leaders ( n = 3). The study found that SFSH was not clearly communicated to students due to the educational structure and chaotic rhythm of the school days, ambivalent attitudes among teachers toward enforcement of smoking rules and lack of clear managerial support. The interplay of these factors counteracted the implementation of SFSH in the VET context. The presented contextual factors are important when interpreting the effectiveness of the Focus intervention and for informing future preventive efforts aiming to reduce smoking among youth in high risk of smoking cigarettes. Lay Summary: Youth represents a crucial period for smoking prevention. School-based interventions show promising effects in this respect. This study presents findings from the qualitative process evaluation of a smoking preventive intervention, Focus, in the vocational school (VET) setting. The aim was to examine the role of context in the implementation process. The data consist of participant observation field notes ( n = 21 school days), focus groups ( n = 8 with students and n =  5 with teachers) and semi-structured individual interviews with VET leaders ( n = 3). The study found that smoke-free school hours was not clearly communicated to students due to several contextual factors, namely an unclear structure and purpose of the school day, ambivalent attitudes among teachers toward smoking rules and lack of managerial support. These factors are important when interpreting the effectiveness of the Focus intervention and for informing future smoking preventive efforts among youth in high risk of smoking cigarettes.